Efektivitas biokonversi limbah kulit kopi sebagai pupuk kompos untuk meningkatkan pertumbuhan bibit kopi arabika di Desa Loa - Ina Darliana; Sri Wilujeng; Dwi Wahyuni (University of Insan Cendekia Mandiri, 2025)
Coffee (Coffea sp.) is one of the contributing commodities of non-timber forest products in the Indonesian economy. Loa Village is one of the coffee producing centers whose land is located among the forest stands of protected forest areas managed by Perum Perhutani, Bandung Regency. To increase the productivity of coffee plants in Loa Village and minimize the environmental impact of coffee skin waste, this study aims to examine the effect of coffee skin waste compost fertilizer on the growth of arabica coffee seedlings in Loa Village. The research was conducted from September to December 2024 at the Faculty of Forestry, Winaya Mukti University using the Completely Randomized Design (CRD) method consisting of 4 treatments and six replications. Treatments: P0 = 0% coffee waste + 100% soil, P1 = 25% coffee waste + 75% soil, P2 = 50% coffee waste + 50% soil, P3 = 75% coffee waste + 25% soil. Observations were carried out for 3 months with an interval of one month. Data collection includes the results of measuring the height and diameter of seedlings that are studied for differences in each treatment using manual average calculations and analyzing their effectiveness using SPSS version 25. The results obtained the best compost fertilizer formulation from coffee skin waste recommended is 25% coffee skin waste compost fertilizer and 75% soil media. This composition significantly increased the height of Arabica coffee seedlings in the 3rd month and stem diameter in the 2nd month after fertilizer application.